PENERAPAN ACOUSMATIC UNTUK MEMBANGUN DIMENSI RUANG PADA TATA SUARA FILM “SEPENGGAL KISAH BUNGA” - Gede Bayu Permana; I Kadek Puriartha; I.B. Hari Kayana Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
Sound design/system is a way for managing and taking advantage of a sound source, it corresponds to the need for a particular purpose, like movies. “Sepenggal Kisah Bunga” is a short fiction movie which falls into a genre of drama. The author who is the sound designer for this film uses the application of acousmatic for developing dimension of space. The purpose of the use of acousmatic is for building the dimension of space to bring the audience closer to the setting of the film, with the result that this work seems real. The author believes in the concept, that it can relay the message well and experiences that the film is real. The implementation of acousmatic is to build the dimensions of space, using a variety of sound dialogue and sound effects, also with sound accuracy which matches the main sound elements of the story setting. Acousmatic means sound that is heard without looking at its origin. During production, the author recorded the analog process and the acousmatic sound effects themselves. However, most of the sound recording process for acousmatic is done during post-production. After all the sounds are gathered it enters the timeline mixing, the author does the editing process with effects to match the main sound elements of the story settings. The author also believes by using audio output 5.1 channel system, which strengthens the usage of acousmatic in building dimensional space. Therefore the author uses the audio output in this film. The author ensures that the use of sound effects and dialogue is not visible in the mise en scene with the sound accuracy that it sounds precise to the setting of the story, hence it shall build the dimension of space. In this movie, you could hear the sound of birds chirping, the dog’s bark, and other pet’s sound. As well as the sound of the surrounding environment that the author created, like the sound of neighbors chatting, and people doing their activities. These sounds are the implementation of acousmatic to build the dimensions of space. With that, the author believes that it can bring the film setting closer to the audiences and make the movie “Sepenggal Kisah Bunga” feel real.